A new HLA‐B allele, B*44:203, sequenced in a Spanish Caucasian cord blood unit. Issue 1 (16th December 2014) - Sánchez‐Gordo, F.; Balas, A.; Gomez‐Zumaquero, J. M.; Prat, I.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐B*44:203 shows one nucleotide difference to B*44:03:01 at codon 171 (TAC>CAC, Y171>H171).